Trinadtsat' . The Thirteen - Romm, Mikhail (Mosfilm, 1936)
Duration: 01:25:00 A unit of horse soldiers, an officer's wife, and a geologist struggle to stay alive in the desert after they are lost during a battle in this Russian drama. The abandoned band end up finding shelter in an empty fortress. Soon they are attacked by 200 enemies. Things look bleak for the survivors until the Russian cavalry rides in to save them. The rhythmic pattern, calculated with the mathematical precision, alternates attacks with pauses, thus never letting the viewer's attention go slack. The film was shot at the location where the last basmach bands had been cruched only 1933, so the bandits' leader became the prototype of the elusive Shirmatkhan. "Thirteen" was to become one of the first Sovier "Easterns", setting a model to emulate by a host of other adventure movies that followed in its wake.